From cognitive capability to social reform? Shifting perceptions of learning in immersive virtual worlds - Maggi Savin-Baden (Association for Learning Technology, 2008)
Learning in immersive virtual worlds (simulations and virtual worlds such as Second Life) could become a central learning approach in many curricula, but the socio-political impact of virtual world learning on higher education remains under-researched. Much of the recent research into learning in immersive virtual worlds centres around games and gaming and is largely underpinned by cognitive learning theories that focus on linearity, problem-solving and the importance of attaining the ‘right answer' or game plan. Most research to date has been undertaken into students' experiences of virtual learning environments, discussion forums and perspectives about what and how online learning has been implemented. This article reviews the literature relating to learning in immersive virtual worlds, and suggests that there needs to be a reconsideration of what ‘learning' means in such spaces.